Circulating miR‐210 as a diagnostic and prognostic biomarker for colorectal cancer. (22nd February 2016) - Wang, W.; Qu, A.; Liu, W.; Liu, Y.; Zheng, G.; Du, L.; Zhang, X.; Yang, Y.; Wang, C.; Chen, X.
Abstract : microRNA‐210 (miR‐210), the master hypoxamir, is overexpressed and generally exhibits oncogenic properties in most human solid tumours, including colorectal cancer (CRC). However, the status of circulating miR‐210 in CRC is still unknown. This study aims to assess the clinical significance of circulating miR‐210 in CRC. Using (reverse transcription quantitative PCR) RT‐qPCR analysis, we compared the expression levels of circulating miR‐210 in serum of 268 CRC patients and 102 healthy controls, and found that serum miR‐210 was significantly higher in CRC than in healthy controls ( P < 0.001). The area under the receiver operating characteristic curve (AUC) of circulating miR‐210 to detect CRC was 0.821, with a sensitivity of 74.6% and a specificity of 73.5%. The AUC of circulating miR‐210 showed significantly higher detection capability than that of carcinoembryogenic antigen ( P < 0.05). Kaplan–Meier analysis demonstrated that increased serum miR‐210 level correlated with reduced overall survival (OS) and disease‐free survival (DFS) ( P = 0.008 and P = 0.008 respectively). Cox analysis indicated circulating miR‐210 was an independent prognostic factor for OS and DFS. Taken together, our data suggested that circulating miR‐210 could be a potential non‐invasive marker for diagnosis and prognosis of CRC.